Modeling ice birefringence and oblique radio wave propagation for neutrino detection at the South Pole. Issue 81 (27th April 2020) - Jordan, T. M.; Besson, D. Z.; Kravchenko, I.; Latif, U.; Madison, B.; Nokikov, A.; Shultz, A.
Abstract: The Askaryan Radio Array (ARA) experiment at the South Pole is designed to detect high-energy neutrinos which, via in-ice interactions, produce coherent radiation at frequencies up to 1000 MHz. Characterization of ice birefringence, and its effect upon wave polarization, is proposed to enable range estimation to a neutrino interaction and hence aid in neutrino energy reconstruction. Using radio transmitter calibration sources, the ARA collaboration recently measured polarization-dependent time delay variations and reported significant time delays for trajectories perpendicular to ice flow, but not parallel. To explain these observations, and assess the capability for range estimation, we use fabric data from the SPICE ice core to model ice birefringence and construct a bounding radio propagation model that predicts polarization time delays. We compare the model with new data from December 2018 and demonstrate that the measurements are consistent with the prevailing horizontal crystallographic axis aligned near-perpendicular to ice flow. The study supports the notion that range estimation can be performed for near flow-perpendicular trajectories, although tighter constraints on fabric orientation are desirable for improving the accuracy of estimates.